The Effectiveness of Pulmonary Rehabilitation on Pulmonary Function among Adults Patients of COVID-19 Survivors: A Systematic Review - Hasanudin Hasanudin; Tintin Sukartini; Makhfudli Makhfudli; Alfian Nur Rosyid; Handira Nadhifatul Aini; Natalia Christin Tiara Revita (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: Corona Virus Infection Disease (COVID-19) refers to the infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Most of COVID-19 survivors have residual symptoms after being discharged from the hospital, it then leads to the decreased lung function and quality of life (QoL). Pulmonary rehabilitation is essential because it can reduce the impact of these sequelae. This study aimed to determine the effectiveness of pulmonary rehabilitation in improving lung function among adult patients of COVID-19 survivors.Methods: This study was conducted using 5 databases, namely: CINAHL, PubMed, SAGE, Science Direct, and Scopus from 1 April 2020 to 30 September 2021. The combination of keywords used was: